The Impact of Message Framing and Source Credibility on Breastfeeding Intention: A Social Marketing Approach - Hussein, Ananda Sabil; Manna, Valerie; Cohen, David (Gadjah Mada International Journal of Business, 2014)
Though highly recommended by health organizations worldwide, breastfeeding an infant from birth for a period of several months is not universal. There is thus a need to investigate appropriate and effective means to promote this breastfeeding behavior. This study, rooted in a social marketing perspective, tests the impact of message framing and source credibility on the behavioral intention to breastfeed. A 2 x 2 factorial experiment was conducted in Indonesia, an especially relevant setting given that the percentage of Indonesian women who breastfeed is low compared to other countries. Two hundred and seventy nine pregnant women participated in this study. The findings of this study indicate that the interaction between message framing and source credibility has a significant effect on a personâs attitude and intention to provide exclusive breastfeeding. In addition, this study finds that attitude is an essential determinant of intention. Â Â Â Â Â Â Â